A Miniaturized Broadband Omnidirectional Monopole Antenna Operating at UHF Band in Wireless Communication. Issue 1 (1st December 2022) - Zhang, Xuan; Zhao, Chunqi; Yang, Yang; Wang, Ren; Zhang, Zhaojing; Li, Jialei
Abstract: In the paper, a miniaturized broadband omnidirectional monopole antenna is designed. The two bending E-shaped structures are introduced into the common two-strip structure monopole antenna. The radiation patches can be effectively distributed on two sides of the dialectic body by four shorting pins. Thus, the proposed antenna has the function of miniaturization and integration. According to the introduced structures, the whole antenna has a smaller size of 318mm*12.2mm, which can improve a 34.2% integration degree. Finally, the present monopole antenna is manufactured, and the measured data shows that it has stable gains and good omnidirectional patterns from 463MHz to 513MHz.